Measuring seated hip extensor strength using a handheld dynamometer: an examination of the reliability and validity of the protocol - Seko, Toshiaki (J Phys Ther Sci, 2015)
[Purpose] The purpose of this study was to examine the reliability and validity of measurements of hip extensor muscle strength using a handheld dynamometer (HHD) with subjects in a sitting position. In doing so, we also aimed to establish a modified method of measurement for patients with flexion contractures in the trunk and lower extremities. [Subjects and Methods] In 20 healthy males, hip extensor muscle strength was measured using a handheld dynamometer in sitting, prone, and standing positions by contracting the hip extensor muscle isometrically with the knee flexed at 90 degrees. For each position, we investigated the relative and absolute reliability and validity of the measurements, and compared muscle strength between the different positions. [Results] The reliability and validity of measurements were highest in the sitting position and higher in both the sitting and standing positions as compared with those in the prone position. [Conclusion] Our findings suggest that measurements taken in a sitting position are accurate in assessing hip extensor muscle strength and would be applicable to patients with flexion contractures in the trunk and lower extremities.